AB0637 Uv-b skin exposure: a possible mode of treatment for vitamin d deficiency and mood disorders. (23rd January 2014) - Biersack, M. G.; Majer, M.; Piazena, H.; Braun, T.; Hoehne-Zimmer, V.; Burmester, G.-R.; Buttgereit, F.; Uebelhack, R.; Detert, J.
Abstract : Background: The prevalence of Vitamin D deficiency in northern countries such as Germany is as high as 60% [1 ]. Vitamin D deficiency is usually defined as 25(OH)D3 levels lower than 50 nmol/l. Insufficiency already starts at levels under 75 nmol/l, which consequentially leads to still more severe figures considering the population's supply status [2 ]. Since Vitamin D is not only essential for calcium hemostasis, but has recently also been detected to play a role in the prevention of autoimmune diseases, carcinogenesis and psychiatric disorders, such as major depression and seasonal affective disorder, a solution for improving the Vitamin D supply is strongly needed. Objectives: UV radiation is necessary for 90% of the body's Vitamin D production and is not sufficiently available in Europe during the winter months [3 ]. Therefore, it was our aim to examine the effect of an artificial UV stimulation on Vitamin D status and mood of young women. Methods: 20 healthy young women, aged 20-30 (Ø 22, 95), were exposed to 3 sessions (on day 1, 3 and 5) of UV-B radiation during one week in winter. The irradiation dose was increased from 80 J/m 2 on day 1 to 150 J/m 2 on day 5 for Fitzpatrick skintype I, and from 100 J/m 2 to 187, 5 J/m 2 for skintypes II and III. All doses applied were below the minimal erythema dose (MED), usually defined as 250 J/m 2 . Before (day 1) and after (day 7) the radiation week blood samples for 25(OH)D3 and 1, 25(OH)2D3 determination were taken, and the subjects were asked to answer the mood questionnaire "Beck Depression Inventory" (BDI). The BDI was also assessed by additional 24 female, healthy controls before and after a week of negligible sun exposure. 4 and 6 weeks later, on day 36 and 50, further blood samples for Vitamin D detection were retained. Results: Both Vitamin D metabolites increased considerably after the 3 UV-sessions: 25(OH)D3 rose from its 54, 4 nmol/l (SD: 24, 1 nmol/l) baseline level to 68, 3 nmol/l (SD 18, 2 nmol/l) on day 7 (p <0, 001), as did 1, 25(OH)2D3 from 130, 9 pmol/l (SD 35, 8 pmol/l) to 157, 1 pmol/l (SD 49, 8 pmol/l) (p= 0, 009). Moreover, we detected still significantly higher 25(OH)D3 levels than at baseline 4 and 6 weeks after UV exposure (p <0, 001 and. p= 0, 044). Interestingly, the BDI also showed an improvement of more than 35%, from a score of 3, 95 (SD 2, 14) to 2, 55 (SD 2, 54) (p= 0, 003) and correlated with both, 25(OH)D3 (-0, 436; p= 0, 005) and 1, 25(OH)2D3 (-0, 42; p= 0, 007). There was no such improvement in the UV-unexposed controls, whose BDI scores did not differ on day 1 and 7. Conclusions: 3 suberythemal UV-B stimulations increase Vitamin D levels and also considerably improve the mood of healthy young women. After further studies with an expanded spectrum of subjects, this method presents one possible solution to the difficult Vitamin D supply situation and can also have a preventive impact on the increasing number of mood disorders. Its application would be especially eligible for diseases such as rheumatoid arthritis, where patients suffer from seriously decreased Vitamin D levels and also have a high prevalence for the co-morbidity of depression. References: DGE 2011 Holick MF. Vitamin D deficiency. Nengl j med 2007;357:3. Webb AR. Who, what, where and when-influences on cutaneous vitamin D synthesis. Prog Biophys Mol Biol. 2006 Sep;92(1):17-25. Disclosure of Interest: None Declared